Tante - Sedgwick, Anne Douglas, 1873-1935 (Salt Lake City, UT : Project Gutenberg, 2009)
"Tante" by Anne Douglas Sedgwick is a novel written in the early 20th century. The story unfolds against the backdrop of musical concerts in London, focusing on the iconic Madame Okraska, a celebrated pianist, and her enigmatic adopted daughter, Karen Woodruff. The relationship between these two characters hints at themes of devotion, artistic ambition, and the weight of personal history as they navigate the complexities of fame and expectation. The opening of the narrative immerses readers in the atmosphere of an eagerly awaited concert in London, where a diverse audience is gathered to witness Madame Okraska's performance. The description captures the anticipation, excitement, and social nuances of the attendees, emphasizing Okraska's unique blend of talent and beauty. As the concert commences, the initial excitement is contrasted by introspective moments experienced by Gregory Jardine, a barrister who becomes intrigued by Karen. Through their interactions, we begin to see the contrasting worlds they inhabit$1 (Bone of public adoration and the other cloaked in personal challenges$1 (Bsetting the stage for deeper explorations of their intertwined destinies. (This is an automatically generated summary.)s
Release date is 2009-09-27
E-text prepared by David Garcia, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Fiction